ANALISIS PENGARUH VOLATILITAS HARGA, LIKUIDITAS SAHAM, EPS, SIZE FIRM, MOMENTUM OVERNIGHT TERHADAP RETURN SAHAM (Studi kasus perusahaan yang terdaftar dalam Indeks LQ45 Periode 2009-2013) - Situmeang, Santa; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to examine the influence of price volatility, earning per share, stock liquidity, firm size, and momentum overnight on Â stock return. Independent variable used in this study were price volatility,earning per share, stock liquidity, firm size, and momentum overnight, while dependent variable was stock return.Research sample in this study were the company on Indeks LQ 45 and listed on the Indonesia Stock Exchange. Time range used in this research Â from Â 2009 until 2013. Sample were taken by purposive sampling method so that obtained 105 samples. Pooled data analysis with random effect model used as analysis method in this research.Pooled data regression analysis results showed that price volatility, earning per share, and momentum overnight had a positive significant effect on stock return. Whereas stock liquidity and size had insignificant effect on stock return. In this research, variance of stock return had been a explained by variance of independen variables as big as 27% and 73% explained by the other variables outside this research.